PENGGUNAAN MODEL PEMBELAJARAN PENEMUAN DALAM PEMBELAJARAN TEKS LAPORAN HASIL OBSERVASI PADA PESERTA DIDIK KELAS X SMA NU JUNTINYUAT - Rahmania, Juju; M. Masrurih; Ade Hasanudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled The Use of Discovery Learning Model in Learning Observation Report Texts for Grade X Students of SMA Nu Juntinyuat. This study is motivated by the ability of students in writing observation report texts which is still very difficult. This study aims to determine the use of discovery learning models on the learning outcomes of writing observation reports for grade X students of SMA Nu Juntinyuat. Thus, the hypothesis of this study is: the effectiveness of the discovery learning model in learning observation report texts in grade X SMA Nu Juntinyuat. This study is a type of quasi-experimental research. The research design used is a pretest-posttest control group design, with research samples consisting of two classes, namely class X 3 as a control class with a total of 22 students and class X 1 as an experimental class with a total of 23 students. This study uses test data collection, observation and documentation of all the data as material to determine the effectiveness of the use of the discovery learning model. Based on the analyzed data, the average learning outcome score for control class X3 using the Discussion method was 73.40, while the average learning outcome score for experimental class X1 using the discovery learning model was 80.22. Therefore, the calculated t-test was greater than the table t-test, i.e., 2.755 > 2.016. This indicates that Ha was accepted and . Thus, the researcher concluded that the application of the discovery learning method to writing observational report texts in class X of SMA NU Juntinyuat was effective.